Thermal conductivity of coconut shell particle epoxy resin composite. Issue 1 (February 2021) - Ismail, I; Hatta, Z N; Mursal,; Jalil, Z; Md Fadzullah, S H S
Abstract: Coconut shell is one of the agricultural wastes that are widely available in Indonesia and other tropical countries. Unfortunately, the coconut shell waste has not been used optimally for new materials, especially for thermal insulation material. In this work, the composite from coconut shell particles using epoxy resin adhesives has been prepared. The particle sizes of coconut shells for composite samples were 60, 80, 100, and 120 mesh. The compositions of samples for each particle size (ratio between coconut shell and epoxy resin) were 70/30, 75/25, 80/20, and 85/15 (vol %). The thermal conductivity of each composite sample has been examined by using a single-plate method. The density of each sample has also been measured. The results showed that the thermal conductivity of composite sample for 60 mesh of particle size with 70/30 vol.% composition was 0.071 W/m K. As the composition of coconut shell was increased to 85 vol.%, the value of thermal conductivity decreased to 0.062 W/m K. It was found that the thermal conductivity of composite sample decreased as the composition of coconut shell was increased. For the composition of 70/30 vol.%, the thermal conductivity increased to 0.078 W/m K for 120 mesh of particle size. This behavior was also the same for other compositions, where the value of thermal conductivity of composite increased as the coconut shell particle size decreased. The density of the composite was found in the range of 0.799 – 0.938 g/cm 3 . As the particle size of the coconut shell was reduced, the density of the composite increased. This study revealed that both thermal conductivity and density of coconut shell epoxy composite are dependent on the particle size of the coconut shell. The thermal conductivity of all samples was less than 0.1 W/m K indicating that the coconut shell epoxy composite is quite potential for thermal insulation.